Development of a paper-and-pencil semi-adaptive questionnaire for 5 domains of health-related quality of life (PAT-5D-QOL). - Kopec, Jacek A; Sayre, Eric C; Davis, Aileen M; Badley, Elizabeth M; Abrahamowicz, Michal; Pouchot, Jacques; Sherlock, Lesley; Esdaile, John M (Quality of Life Research, 2013)
Objectives: To develop a paper-and-pencil semi-adaptive test for 5 domains of health-related quality of life (PAT-5D-QOL) based on item response theory (IRT).Methods: The questionnaire uses items from previously developed item banks for 5 domains: (1) walking, (2) handling objects, (3) daily activities, (4) pain or discomfort, and (5) feelings. For each domain, respondents are initially classified into 4 functional levels. Depending on the level, they are instructed to respond to a different set of 5 additional questions. IRT scores for each domain and overall health utility scores are obtained using a simple spreadsheet. The questions were selected using psychometric and conceptual criteria. The format of the questionnaire was developed through focus groups and cognitive interviews. Feasibility was tested in two population surveys. A simulation study was conducted to compare PAT-5D-QOL with a computerized adaptive test (CAT-5D-QOL) and a fixed questionnaire, developed from the same item banks, in terms of accuracy, bias, precision, and ceiling and floor effects.Results: Close to 90 % of the participants in feasibility studies followed the skip instructions properly. In a simulation study, scores on PAT-5D-QOL for all domains tended to be more accurate, more precise, less biased, and less affected by a ceiling effect than scores on a fixed IRT-based questionnaire of the same length. PAT-5D-QOL was slightly inferior to a fully adaptive instrument.Conclusions: PAT-5D-QOL is a novel, semi-adaptive, IRT-based measure of health-related quality of life with a broad range of potential applications.